2020
DOI: 10.7226/jtfm.26.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Ecotourism Policy Research Trends in Indonesia, Japan, and Australia

Abstract: Numerous definitions and concepts regarding ecotourism lead to different implementations in ecotourism policies and systems. Identifying trends between countries provide valuable information for the development of inadequate ecotourism sites. This study aimed to understand the trends in ecotourism policies in Japan, Indonesia, and Australia by examining the bibliographic records of existing ecotourism policy research. These records were retrieved from the Scopus database and processed by using the scientometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…To organize ecotourism activities following local culture and natural sites in each region, members are associated with 17 local organizations (Fukamachi, 2017). Since the policy was launched, research has surged and varies from the community, conservation, and traditional knowledge to the benefits of the ecotourism industry (Sisriany & Furuya, 2020). The Ecotourism Promotion Council defines ecotourism as responsible travel that allows travelers to experience and learn about the natural environment, history, and culture.…”
Section: How Japan Promotes Ecotourismmentioning
confidence: 99%
“…To organize ecotourism activities following local culture and natural sites in each region, members are associated with 17 local organizations (Fukamachi, 2017). Since the policy was launched, research has surged and varies from the community, conservation, and traditional knowledge to the benefits of the ecotourism industry (Sisriany & Furuya, 2020). The Ecotourism Promotion Council defines ecotourism as responsible travel that allows travelers to experience and learn about the natural environment, history, and culture.…”
Section: How Japan Promotes Ecotourismmentioning
confidence: 99%
“…Ecotourism activities oriented to natural resources, natural ecosystems, and have not been polluted must minimize negative impacts on the environment and local socio-cultural (Butarbutar and Soemarno 2013). Developing trends in ecotourism policies in Indonesia are conservation, ecology, and community participation (Sisriany and Furuya 2020). Based on the ODTWA potential of Nya'deng Lake, the orientation of ecotourism policies must be based on conservation, empowerment of local communities, and integrated planning with local governments.…”
Section: Potential Attractions Of Nya'deng Lakementioning
confidence: 99%
“…Regarding ecotourism, it is possible to find several academic studies. Some studies focus on ecotourism as a learning tool (Mondino, Beery, 2019), role of ecotourism in sustainable tourism development (Salman et al, 2020), ecotourism potential of destinations (Safarabadı, 2016;Güler, 2021), carrying capacity within ecotourism (Butarbutar, Soemarno, 2013;Zhao, Jiao, 2019)planningand design (Shang et al, 2020;Sisriany,Furuya, 2020;Aryal et al, 2019;Cohen, Silva, 2010), research topics benefiting from meta-analysis (Wondirad, 2019), tourists' intention to participate in ecotourism (Pham, Khanh, 2020;Ren et al, 2021;Lee et al, 2020;Handriana, Ambara, 2016), intentions of locals/residents toparticipate in ecotourism (Wu, Chen, 2018;Landra et al, 2018;Mogoria et al, 2018;Lim et al, 2017;Wanga et al, 2013;Menon, 2019;Adeleke, 2015;Zhang, Lei, 2012). Mondino and Beery (2019) have investigated ecotourism as a learning tool benefiting from a case study and have found out that ecotourism activities supported collaboration between stakeholders, but because of insufficient environmental education (language, method, and course related problems at higher governmental levels) there were still negative perceptions of the sides.…”
Section: Ecotourismmentioning
confidence: 99%
“…According to the results, transportation, water, animal, plant, and ecotourism resources were found as strengths; and theme, staff quality as weaknesses; and government support, combination of local culture with tourism, and increased demand as opportunities and competition among peers, and different tourist demands as threats. Sisriany and Furuya (2020) have investigated ecotourism policy research trends in Indonesia, Japan, and Australia benefiting from scientometrics analysis (Totally 430 academic studies). Related with ecotourism, top keywords included conservation for Indonesia, biodiversity for Japan, and management for Australia.…”
Section: Ecotourismmentioning
confidence: 99%